(untitled) (Journal of the College of Basic Education, 2022)
In her study, the researcher touched on some of the visual abilities that are related to sports performance, especially if they are not accurately mastered, and attention is paid to addressing the weaknesses in those abilities as they negatively affect the level of performance. By informing the researcher of the results of matches related to the game of table tennis and the investigation and search for the most important reasons that cause failure in the level of performance, the researcher noted a weakness in the aspect of visual abilities as a game that depends on the transfer of information from the external environment to the brain to be interpreted and dealt with accurately, as each skill Athletic, the kinetic side and the visual side must be highly efficient in order to positively affect the level of performance. Since the skills of this game are diverse and different and require focus and attention to mental abilities in addition to visual abilities being no less important than them, so the researcher wanted to shed light on visual accuracy and visual tracking and their relationship to the accuracy of transmission in table tennis. Being one of the basic offensive skills in this game, which is characterized by the small size of the ball, the difference in its strikes and the speed of its movement, and all that was mentioned confirms the efficiency, development and upgrading of visual abilities to contribute to improving the level of mental and skill abilities. The study aimed to identify the correlation of the selected visual abilities with the accuracy of serving in table tennis, and the study also aimed to extract the percentage of contribution to those abilities with the accuracy of the serve. The hypotheses of the research were that there is a significant correlation between the optical accuracy and the optical tracking with the accuracy of the transmission, and there is a contribution ratio between those capabilities with the accuracy of the transmission. The researcher used the descriptive approach to extract the correlation relationship as it is more appropriate to the research problem on a sample of the national team players in the Kadhimiya Club, which numbered (8) players who were chosen by the intentional method. Conducting visual and skill tests at the National Center for Sports Talent. The method of testing and how to score points and the number of attempts for each laboratory were explained, and the researcher was keen to ensure that the conditions were appropriate and the same for all testers. Visual abilities Visual accuracy and visual tracking with accuracy of transmission in table tennis. The researcher recommended the necessity of paying attention to visual abilities, as they are no less important than mental and skill abilities, and any weakness in those abilities negatively affects the level of performance.